Interval waktu iskemia, derajat iskemia, dan sindrom kompartemen merupakan faktor risiko amputasi pada pasien acute limb ischemia yang dilakukan tindakan trombektomi terbuka di RSUP Sanglah Denpasar - Dea Emmanuel; Ketut Putu Yasa; Ida Bagus Putra Manuaba; I Nyoman Semadi; Ketut Widiana; Gede Wirya Kusuma Duarsa (DiscoverSys Inc., 2020)
Introduction: Acute Limb Ischemia (ALI) is a sudden decrease in perfusion in the extremities that causes the threat of tissue viability and is still one of the causes of disability. The purpose of this study was to determine the factors that influence amputation in patients with acute limb ischemia who undergo thrombectomy.Methods: This was a retrospective observational study with case-control studies. As many as 40 patients with acute limb ischemia who underwent thrombectomy were seen as an outcome of amputation. Matching was done based on age and sex in the case (amputation) and control (without amputation) groups. Data collection is based on medical records from 2014 to 2019. Bivariate analysis uses Chi-Square or Fisher's Test while multivariate analysis uses logistic regression.Results: In this study we found that the time interval of ischemia and the degree of ischemia is a risk factor of amputation in person with ALI (p<0.05) but compartment syndrome was not significantly related to amputation in ALI. Multivariate analysis shows degree of Rutherford IIB / III ischemia to be a the most dominant factor for amputation (OR = 6.84; 95% CI = 1.19-39.35; p = 0.03).Conclusion: The time interval of ischemia and the degree of ischemia are factors that influence amputation in patients with acute limb ischemia who undergo thrombectomy. The degree of ischemia is the most dominant risk factor affecting amputation.Â Latar Belakang: Acute Limb Ischemia (ALI) adalah penurunan secara tiba-tiba perfusi di ekstremitas sehingga menyebabkan ancaman viabilitas jaringan dan masih menjadi salah satu penyebab disabilitas Tujuan dari penelitian ini adalah untuk mengetahui faktor faktor yang mempengaruhi amputasi pada pasien acute limb ischemia yang dilakukan trombektomi.Metode: Penelitian ini merupakan penelitian observasional retrospektif dengan studi kasus kontrol. Sebanyak 40 pasien acute limb ischemia yang dilakukan trombektomi dilihat outcomenya dari amputasi. Dilakukan matching berdasarkan usia dan jenis kelamin pada kelompok kasus (amputasi) dan kontrol (tanpa amputasi). Pengambilan data berdasarkan catatan medis dari tahun 2014 hingga 2019. Analisa bivariat menggunakan Chi-Square atau Uji Fisher sedangkan analisa multivariat menggunakan regresi logistik.Hasil: Berdasarkan analisa statistik didapatkan didapatkan interval waktu iskemia dan derajat iskemia mempengaruhi amputasi (p<0,05) namun sindrom kompartemen tidak berhubungan secara signifikan. Hasil multivariat dengan regresi logistik ditemukan derajat iskemia Rutherford IIB/III menjadi faktor dominan terjadinya amputasi (OR = 6.84; IK 95% = 1,19-39,35; p = 0,03).Simpulan: Interval waktu iskemia dan derajat iskemia merupakan faktor yang mempengaruhi amputasi pada pasien acute limb ischemia yang dilakukan trombektomi. Derajat iskemia merupakan faktor risiko yang paling dominan mempengaruhi amputasi.